Independensi Mahkamah Konstitusi dalam Proses Pemakzulan Presiden dan/atau Wakil Presiden - Abdul Wahid (The Constitutional Court of the Republic of Indonesia, 2014)
It has been highlighted in the constitution that the Constitutional Court has one obligation to give verdict on the House of Representatives’ (DPR) opinion regarding the impeachment of the president and/or the vice president. Obligation given by this constitution is about to prove that Indonesia is a law state. Even though the Constitutional Court has become part of the dismissal process of president and vice president, the independence of its obligation is doubted by public because of the recruitment factors of the Constitutional Court judges. Even though these judges successfully give verdict because the president or the vice president is proven to break the law, it does not mean that its verdict absolutey ties the authority of the House of Assembly (MPR).